Genome sequence of Acidovorax avenae strain T10_61 associated with sugarcane red stripe in Argentina - Fontana, Paola Daniela (2016)
Red stripe of sugarcane in Argentina is a bacterial disease caused by Acidovorax avenae. The genome sequence from the first isolate of this bacterium in Argentina is presented here. The draft genome of the A. avenae T10_61 strain contains 5,646,552 bp and has a G+C content of 68.6 mol%.